PELATIHAN SISTEM MANAJEMEN ARSIP DI KANTOR DESA JAYA MULYA - Wahid, Mahfud Rohman; Sulastri, Tuti; Rofieq, Ainur (An-Nizam, 2024)
Outgoing and incoming letters are active dynamic archives whose usage levels are still high. The birth of the e-Government concept makes it easier to administer government by utilizing technology. Dynamic archive management which is still manual causes many shortcomings such as damaged archives, lost archives, difficult to find etc. Therefore, a digital archive management system is needed so that dynamic archive management is more effective. Service activities related to archive management system training were carried out in Jayamulya Village, Serang Baru, Bekasi. The method used is by providing materials, training and practice in managing records of outgoing and incoming letters using an records management system. As a result of this service activity, village officials know, understand, practice and use the archive management system so that outgoing and incoming mail management is more effective. Although the archives management system still needs to be developed to make it easier and more effective in managing archives at the Jayamulya Village Office.